Fostering Students’ Learning in the 21st Century: Effect of Inquiry-Based Learning on Students’ Achievement of Science Process Skills in Biology Subject - Joy, Wabuke M.; Dinah , Samikwo C. (African Journal of Education,Science and Technology (AJEST), 2017)
The study investigated the effectiveness of Inquiry-Based Learning Approach (IBL) on students’ achievement of Science Process Skills (SPS) among secondary level Biology students. Globally there is still a challenge in determining which teaching method equips students with both knowledge and skills which are not only useful for the realization of sustainable development goals (SDGs), but are also required for the 21st century. The Solomon Fourfold Non-Equivalent control group design was employed in the study. The study was carried out in Wareng sub county of Uasin Gishu County, Kenya where there has been persistent low achievement in Biology subject. The study sample comprised of 220 students selected from form three students in four different mixed day secondary schools. The sampling techniques used were stratified, systematic and simple random sampling. The experimental groups received instructions through IBL approach and control groups using the Traditional Learning (TL) method. Biology Science Process Skills Achievement Test (BSPSAT) was used for data collection. The results of the study indicated that students in the experimental groups outperformed the control groups in the achievement of selected Science Process Skills. It was concluded that IBL had a positive output on students’ achievement in BSPSAT than the Traditional Learning (TL) method. Teachers of Biology in Kenya should be encouraged to incorporate IBL in teaching so as to enhance the development of Science Process Skills among secondary school students.